Work Period as one of The Risk Factors of Suspected Carpal Tunnel Syndrome (CTS) among Worker in the “X” Furniture Manufacturing, Gresik-East Java 2018 - Dyandarasmi Larasati; Sulistiawati; Andre Triadi Desnantyo (Surabaya Physical Medicine and Rehabilitation Journal, 2022)
Background: Carpal Tunnel Syndrome (CTS) is a nerve disorder where an entrapped median nerve in the carpal tunnel causes pain and numbness in the hand. Prolonged condition of CTS will decrease someone’s productivity in daily life that requires hand. Aim: This study aimed to analyze age, sex, and work period as the risk factors that can increase the incidence of suspected CTS in workers at the "X" Furniture Manufacturing, Gresik, East Java. Material and Methods: An analytic observational cross-sectional study, was conducted in August 2018. A number 47 worker of “X” furniture manufacturing in Gresik, East java, counted as samples obtained by consecutive sampling technique. The data were taken by questionnaires and checked by using the Phalen test. The correlation between the risk factors of age, sex, and work period with suspected Carpal Tunnel Syndrome (CTS) were analyzed using chi-square and Fisher exact test. Results: Based on the research, as many as 15 respondents had suspected CTS. Based on the chi-square test, the significance value between suspected CTS with the risk factor of age are p=0.659, sex are p=0.70, and Fisher exact test resulted in the significance value between suspected CTS with work period are p=0.020. Conclusion: There was a significant difference between suspected Carpal Tunnel Syndrome (CTS) with work period (p<0.05) and there were no significant difference between suspected Carpal Tunnel Syndrome (CTS) with age and sex (p>0.05).